Verhaeren et le peuple - Legavre, Léon; Gailliard, F. (Bruxelles : L' Eglantine, 1927)
Bibliotheek E. Anseele
Bibliotheek Camille Huysmans
Dedicator: Legavre, Léon, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: Verhaeren, Emile